Optimization of a Lightweight HUB Bearing Unit for Racing Cars - Application of Topology Optimization and Additive Manufacturing on a Lightweight HUB Bearing Unit - Sjöberg, Alva; Stomberg, Malin (My University, 2025)
This report describes the product development process for redesigning a bearing application for racing cars with the intent of reducing weight without affecting performance. The project was carried out in collaboration between AB SKF and Chalmers University of Technology. Today, AB SKF manufactures the HBU bearing with traditional manufacturing methods. The aim of this bachelor’s thesis is to develop a design concept suitable for the additive manufacturing technology Powder Bed Fusion Laser Beam. This project followed an iterative design process, starting with brainstorming potential design aspects such as lattice structures and different ear placements, as well as clarifying the criteria. The design process started with a topologically optimized body of an HBU to identify areas where material could be removed. Each concept was visualized using topology optimization software and evaluated using Finite Element Design under conditions similar to real life. The process involved four topology optimization iterations, with each step tackling different problems and achieving improved results. The fourth iteration leads to the final design. Concepts that cleared the yield stress and deformation limit were weighed against each other on the criterion in weight saving percentage and maximum deformation value where the criterion was assigned a weighting factor depending on its importance. The most important criterion was weight reduction. The final concept has a weight reduction of 17,5% compared to the original HBU. The concept is designed to be optimal for PBF-LB by avoiding overhang angles bigger than 45 degrees, not consisting of any closed off holes as well as reducing the amount of support structures needed. In conclusion, using PBF-LB is beneficial because it provides a high level of design freedom resulting in a high level of customization. It allows a component to be optimized for a specific application.
Keywords: Bearing; Powder Bed Fusion Laser Beam; Metal Additive Manufacturing; AB SKF; Product development; Topology optimization